Hubungan Faktor Sosial Ekonomi Dengan Ketahanan Pangan Rumah Tangga Pedagang Sayur Eceran di Pasar Oeba - Sitanaya, Febriyani; Aspatria, Utma; Boeky, Daniela L. A. (Faculty of Public Health, Nusa Cendana University, 2019)
The success of the development is influenced by several aspects, one of them is food security. Food security can be a reflection of the quality of a nation. A nation with low food security can influence its physical and human development. GFSI states that Indonesia occupies 69 positions in World Food security. Food security can not only be seen in terms of global area but also in terms of households. Greengrocer is the person who works in the informal sector and generally has low income. This research aims to see the relationship between income, family largeness, education, and nutritional knowledge of mothers toward greengrocers’ household food security in Oeba Market. This research is a qualitative research type that uses the cross-sectional approach. The research was conducted in Oeba Marketon 74 greengrocers as the sample. The data were analyzed using univariate and bivariate analysis with chi-square statistical tests. The results showed that the income variable (p=0.016) was the variable that affected food security, while the variable that had no effect was family size (p=0.964), education (p=0.552), and nutritional knowledge (p=0.749). Household income is a source of meeting food and non-food needs. Household income is also able to influence the quality and quantity of food purchased. To achieve household food security, family empowerment needs to be given special attention because food shortages both in quantity and quality can inhibit the fulfillment of family nutrition which will result in poor nutritional status in family members.